Rural urban differences in body image perception, body mass index and dieting behaviour among malay adolescent Malaysian schoolgirls - Omar Dev, Roxana Dev; Vasanthi Permal,; Omar Fauzee, Mohd Sofian (European Journals, Inc., 2009)
Body image plays an important role in managing one’s body weight especially in female youth. This research identifies the different body image perception, body mass index (BMI) and dieting behavior among female secondary school students in urban and rural area of Gombak district, Malaysia. Body mass index (BMI) was carried out on 200 Malay students at four secondary schools around Gombak. It was found that there is no significant difference in BMI of female students in the urban secondary schools (19.27 ± 3.83kg/m²) and rural secondary schools (18.65 ± 3.60kg/m²). Respondents answered questions regarding demography and body silhouette chart. Average age of respondents in urban area is 14.53 ± 0.520 years with a family income of RM4570 ± 1890 and the rural area is 14.56 ± 0.47 years with a family income of RM1690 ± 580 (p=0.002, p<0.05). Body image perception was done by asking the respondents to identify own body image through five picture diagrams provided (Body Silhouette Chart). Although more of urban respondents giving inaccurate perception compared to rural respondents, however there is no significant difference in body image perception as compared to body mass index among urban and rural respondents [t(198)=1.18, p=0.23, p>0.05]. But there is significant difference between urban and rural respondents in the body image perception and the desired body image [t(198)=4.57, p<0.05]. Overweight was found to occur among urban female as compared to rural female adolescents because of the economic status of the urban adolescents being higher than their rural counterparts. Furthermore, body image perception among urban and rural adolescents differ from their mother’s perception. Meanwhile, Index of Mild Dieting showed high and moderate mean scores while Index of Extreme Dieting Behaviour showed moderate and low mean scores, indicating that the respondents generally were some what taking actions to control their dietary intake. Urban adolescents seemed to score more on the Index of Mild Dieting and Index of Extreme Dieting Behaviour, significant differences were seen with their rural counterparts (t=3.2, p=0.02; p<0.05) and Rural Urban Differences in Body Image Perception, Body Mass Index and Dieting Behaviour Among Malay Adolescent Malaysian Schoolgirls 70 (t=2.45, p=0.03; p<0.5) respectively. The result of this research shows that body image and dieting behavior should also be given more attention in promoting healthy living style especially among female adolescents.